2022
DOI: 10.21037/atm-22-1045
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-eight months progression-free survival after pyrotinib therapy for HER2-positive recurrent ovarian clear cell carcinoma: a case report

Abstract: Background: Ovarian cancer (OC) is the seventh most common newly diagnosed cancer in women worldwide. Ovarian clear cell carcinoma (OCCC) is a specific type of epithelial ovarian cancer with a poor prognosis. It has been revealed that human epidermal growth factor receptor 2 (HER2)-positive (2+/3+) has been observed in 14% to 45.6% of patients with OCCC. Anti-HER2 therapy has been demonstrated to be an effective strategy for the treatment of HER2-positive breast cancer. However, the role of anti-HER2 therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, in the absence of standard treatment for OCCC and with immunotherapy demonstrating initial success in other tumors, there is an urgent imperative to identify tumour-specific antigens of OCCC. While there is still little research on targeted therapies for OCCC, a team from Zhongshan Hospital in China recently revealed a case of a patient with advanced Human epidermal growth factor receptor 2 (HER2) -positive OCCC, who was treated with pyrotinib and achieved a PFS of 28 months [55]. This study was based on the fact that the HER2 is positively expressed in 14-45.6% of patients with OCCC [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the absence of standard treatment for OCCC and with immunotherapy demonstrating initial success in other tumors, there is an urgent imperative to identify tumour-specific antigens of OCCC. While there is still little research on targeted therapies for OCCC, a team from Zhongshan Hospital in China recently revealed a case of a patient with advanced Human epidermal growth factor receptor 2 (HER2) -positive OCCC, who was treated with pyrotinib and achieved a PFS of 28 months [55]. This study was based on the fact that the HER2 is positively expressed in 14-45.6% of patients with OCCC [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (34) additionally revealed that for HER2-positive advanced gastric cancer patients who have developed a resistance to trastuzumab, pyrotinib is a promising new treatment that can be used as salvage therapy. In a recent case, a patient treated with pyrotinib yielded a PFS of 28 months, a promising result for the use of pyrotinib in treating HER2-positive ovarian clear cell carcinoma (32). Whether or not pyrotinib is effective in trastuzumabresistant MOC is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Because targeting HER2 has been a pivotal treatment strategy for HER2-positive breast cancer, the strategy has potential promise for treating HER2-positive ovarian cancer. Importantly, a case of successful treatment with pyrotinib for HER2-positive ovarian cancer ( 32 ). We have a surprising treatment result of using pyrotinib on an ovarian cancer patient whose HER2 study was positive.…”
Section: Discussionmentioning
confidence: 99%